A Doherty Power Amplifier with Large Back-Off Power Range Using Integrated Enhancing Reactance. (15th April 2018) - Kong, Wa; Xia, Jing; Meng, Fan; Yu, Chao; Yang, Lixia; Zhu, Xiaowei
Abstract : A symmetric Doherty power amplifier (DPA) based on integrated enhancing reactance (IER) was proposed for large back-off applications. The IER was generated using the peaking amplifier with the help of a desired impedance transformation in the low-power region to enhance the back-off efficiency of the carrier amplifier. To convert the impedances properly, both in the low-power region and at saturation, a two-impedance matching method was employed to design the output matching networks. For verification, a symmetric DPA with large back-off power range over 2.2–2.5 GHz was designed and fabricated. Measurement results show that the designed DPA has the 9 dB back-off efficiency of higher than 45%, while the saturated output power is higher than 44 dBm over the whole operation bandwidth. When driven by a 20 MHz LTE signal, the DPA can achieve good average efficiency of around 50% with adjacent channel leakage ratio of about –50 dBc after linearization over the frequency band of interest. The linearity improvement of the DPA for multistandard wireless communication system was also verified with a dual-band modulated signal.